Let f(x) = x - 3 and g(x) = x + 11. Find f(x) · g(x).
2 answers:
Answer:
D
Step-by-step explanation:
(x-3)(x+11)=x^2+11x-3x-33=x^2+8x-33
Answer:
i think its D
f(x) = x-3 and g(x) = x+11
f(x) *g(x) = (x-3)(x+11) = x^2 +11x -3x -33 = x^2 +8x -33
hope this helped :3
You might be interested in
Answer:
9
Step-by-step explanation:
Answer: Yes She is correct
Step-by-step explanation:
Answer:
y=4
Step-by-step explanation:
y=-2/3x+4
y=-2/3(0)+4
y=0+4
y=4
B. 2/3
bcuz there are 3 slices and 2 of them are shaded
There is 7 dimes and 13 pennies